Promoting social bonds for impact investments in Asia. (Manila Asian Development Bank, 2021)
The social bond market has grown rapidly amid the coronavirus disease (COVID19) pandemic. This report explores ways of maximizing the impact of social bonds for sustainable development and of supporting a well functioning social bond market. It analyzes the impact areas that social bonds have addressed to date and introduces the impact measurement techniques that are in use and under development. It notes the need for common standards of information disclosure and impact measurement.
Keywords: Finance -- Asia; Social bond -- Asia; Electronic books